Banjar Local Wisdom as a Dialectic in MI Arabic Language Teaching: A Comparative Analysis Between Formal Curriculum and Nusantara Islamic Values - Mahmudah Mahmudah; Muhammad Adli Nurul Ihsan; Hanna Nova Astuty (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
This study examines the dialectic between Banjar local wisdom and Arabic language pedagogy in Islamic Elementary Schools (MI) through the lens of Nusantara Islam. It addresses the critical tension between text-centric formal curricula and the sociocultural realities of students. Utilizing a Systematic Literature Review (SLR) and Comparative Meta-Synthesis, the research identifies that conventional, formalistic approaches often result in low student engagement and cultural detachment. Findings demonstrate that integrating Banjar values—such as papadah, pantun, and gotong royong—transforms Arabic instruction into a communicative, humanistic, and relevant process. The study culminates in the "Transformational Dialectical Conceptual Model," positioning local wisdom not merely as a teaching aid but as an epistemic foundation for pedagogy. This model redefines Arabic learning as a medium for character formation and cultural identity reinforcement. These results offer a strategic framework for developing localized curricula and contextual teacher competencies, providing a new direction for Indonesian basic Islamic education.